Can the spread of non-native oysters (Crassostrea gigas) at the early stages of population expansion be managed? - Guy, C.I.; Roberts, David (Marine Pollution Bulletin, 2010)
The Pacific oyster (Crassostrea gigas) was introduced into Strangford Lough, Northern Ireland in the 1970s. It was assumed that local environmental conditions would not facilitate successful reproduction. However, in the 1990s there were reports of C. gigas outside licensed aquaculture sites and this investigation set out to ascertain the current distribution, years of likely recruitment and population structure of the species. C. gigas were found distributed widely throughout the northern basin during surveys; the frequency distribution suggesting C. gigas is not recruiting every year. Establishment of feral populations of C. gigas elsewhere have linked to habitat change. A pilot cull was initiated to assess the success rate of early intervention. This paper demonstrates the potential benefits of responding rapidly to initial reports of non-native species in a way that may curtail establishment and expansion. The method advocated in simple and can be recommended to the appropriate regulatory authorities.